Moment-curvature response of concrete beams reinforced with steel bars and dual hooked-end fibers: Tests versus predictions by Model Code 2020 and Rilem TC 162-TDF - Amarjeet Kumar; Aleksandr Sokolov; Alinda Dey; Karolis Sakalauskas; Darius Bacinskas; Juozas Valivonis; Gintaris Kaklauskas (Case Studies in Construction Materials)
The moment-curvature behavior of steel fiber-reinforced concrete (R/SFRC) elements plays a crucial role in deformation analysis and design. While the stress-strain response of conventional concrete structures is relatively straightforward for compressive concrete and tensile reinforcement, the tensile behavior of steel fiber-reinforced concrete is complex and challenging to characterize due to its residual stress-strain relationship. This study investigates the flexural behavior of R/SFRC beams, including longitudinal reinforcement and 0.6 % dual-hooked-end steel fibers from the DRAMIX 4D series. Residual flexural tensile strength was determined in accordance with RILEM TC 162-TDF and Model Code 2020 guidelines by standard three-point bending tests on notched prismatic specimens. The residual flexural tensile strength was determined according to RILEM TC 162-TDF and Model Code 2020 guidelines through standard three-point bending tests on notched prismatic specimens. Further, the beams with varied reinforcement ratio and bar diameter were tested under four-point bending, and the experimental moment-curvature relationships were obtained using both Digital Image Correlation (DIC) and Linear Variable Differential Transformer (LVDT) methods. The study reveals that the DIC-based approach is equally consistent to the LVDT-based method. The predicted moment-curvature responses were calculated using the residual strength parameters and compared with the experimental results. A comprehensive statistical analysis was performed to evaluate the accuracy of the moment-curvature predictions by the codes, revealing that RILEM TC 162-TDF tended to produce stiffer predictions, whereas Model Code 2020 demonstrated better performance with 75 % and 82 % accuracy for R/SFRC beams reinforced with 10 mm and 12 mm diameter steel bars respectively. Notably, both models exhibited improved predictive capabilities at higher reinforcement ratios compared to lower ones. Furthermore, an inverse technique was employed to derive the residual stress-strain relationship of RC structures directly from the experimental moment-curvature diagram. A comparative analysis was then conducted between the code-predicted and experimentally-derived residual stress-strain relationships, which also revealed that Model Code 2020 predictions closely matched the experimental data, especially at higher reinforcement ratios. The study emphasizes the need for careful selection of prediction models and measurement approaches to accurately predict the flexural behavior of R/SFRC members.